ROLE STRESS DAN TURNOVER INTENTION: STUDI EMPIRIS MENGGUNAKAN PERSPEKTIF TEORI PERAN - Sukarta, Made Andy Pradana; Dananjaya, Ida Bagus Gede; Setyastrini, Ni Luh Putri (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
As professionals, Tax Consultants and their employees within a Tax Consulting Office (KKP) provide education, development, and thorough planning to ensure the successful implementation of tax obligations. Differences in opinions between taxpayers and fiscal authorities also represent situations where Tax Consultants and their employees cannot escape role stress in their jobs. This is due to boundary-spanning activities (BSA) that are highly susceptible to role stress. The experienced stress can trigger discomfort at work, thus increasing the desire to change jobs and seek other employment alternatives. In this context, turnover intentions can be triggered by role stress. The population in this study includes all Tax Consultants working at the Tax Consulting Offices (KKP) in Bali Province who hold a practice license. The sample was selected using the purposive sampling method. The selection criteria for the sample members were: (1) active status not limited by position, whether as Partner, Manager/Assistant Manager, Supervisor, or Junior Consultant; (2) a minimum of one year of employment. Primary data was gathered through questionnaires and then processed using SPSS statistical software to determine whether hypotheses were rejected or accepted. The variables used in the study will each be detailed in indicators and subsequently transformed into questionnaire items in the research instrument. Data collection involved questionnaires followed by validity and reliability tests. The data analysis technique used was multiple linear regression. The study's findings indicate that tax consultants' intentions to leave their jobs are affected by role conflict, role ambiguity, and role overload, partially and simultaneously.